2009
DOI: 10.4103/0974-9233.48862
|View full text |Cite
|
Sign up to set email alerts
|

Bleb-related endophthalmitis: Clinical presentation, isolates, treatment and visual outcome of culture-proven cases

Abstract: Purpose:To investigate clinical features, causative organisms and their antibiotic sensitivity, management, and visual acuity outcomes of eyes with bleb-related endophthalmitis (BRE).Design:Retrospective, noncomparative, consecutive eye series.Methods:Clinical and microbiological records of patients with culture positive bleb-related endophthalmitis treated at a single institution between April 1995 and February 2002 were revised retrospectively.Main Outcome Measures:Final visual acuity, loss of eye and compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Final visual outcomes of NLP have been reported in 23–35% of eyes (Busbee et al. ; Ba'arah & Smiddy ; Al‐Turki et al. ), and vision worse than 20/400 has been reported in 43–68% of eyes (Mandelbaum & Forster ; Phillips et al.…”
Section: Prognosismentioning
confidence: 99%
“…Final visual outcomes of NLP have been reported in 23–35% of eyes (Busbee et al. ; Ba'arah & Smiddy ; Al‐Turki et al. ), and vision worse than 20/400 has been reported in 43–68% of eyes (Mandelbaum & Forster ; Phillips et al.…”
Section: Prognosismentioning
confidence: 99%
“…In one study there was no significant difference between VA outcomes of eyes with Streptococcus sp., non- Streptococcus Gram-positive organisms, and Gram-negative organisms 2. Another study showed no significant difference between VA outcomes of eyes with Streptococcus and Staphylococcus sp 3. Others reported VA outcomes for eyes with Streptococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Another study showed no significant difference between VA outcomes of eyes with Streptococcus and Staphylococcus sp. 3 Others reported VA outcomes for eyes with Streptococcus sp. and non- Streptococcus organisms but did not perform a comparative analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Hypopyon was present in all our cases. However, hypopyon absence is noted in previous BAE cases [8]; the significance of this absence must not be underemphasized.…”
Section: Discussionmentioning
confidence: 99%